Wild Cat Valley, Riley County - Morris, Marty (Kansas State University, The Chapman Center for Rural Studies, 2010)
Northwest of Manhattan, Kansas, in Riley County is the location of a valley once called Wild Cat, not only filled with beautiful trees and rolling hills but with the quietness of a community that was once inhabited by many.
Marty Morris, “Wild Cat Valley, Riley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/28.
Keywords: Fort Riley; Junction City; Marty Morris; Samuel Dexter Houston; Wildcat Creek; Riley County